(untitled) (Contemporary Journal of Social Science Review, 2025)
The determination of pre-admission factors affecting agriculture graduate students’ better academic performance measured through cumulative grade point average (CGPA) is the aim of this research. The statistical population consists of 185 first year agricultural graduates enrolled during 2023-24 at the University of Agriculture Faisalabad, Pakistan. The study applies binary logistic regression model on the information collected from the sample respondents. Results reveal that female students are found to be highly successful in achieving CGPA higher than 3 compared to their male fellows. Similarly, entry test held for admission onto agriculture degree program is positively and highly significant predictor of favorable academic achievement. Those students who after graduation have wide preferences for the job also have more chances of achieving better academic performance. The way they select the agriculture degree for study has insignificant effect on specified academic achievement. It is emphatically suggested to continue entry test procedure as a pre-requisite for student’s admission onto higher studies in order to give better graduates to the labor market. Lastly, the government should ensure more jobs in partnership with private sector to absorb future leaders especially females from agriculture sector.